GREEN TECHNOLOGY ON TANNING PROCESS BY EXHAUSTED TANNING SYSTEM - Anggriyani, Emiliana; Nugroho, Alfani Risman (MATTER: International Journal of Science and Technology, 2018)
This study aims to determine the difference of chromium absorption into the skin and difference the shrinkage temperature in chrome mineral tanning by exhausted tanning system and conventional tanning system. The material used were sheep skins. The first treatment by conventional tanning process. The second treatment was tanning process by exhausted system. Tanning process with exhausted system was done by adding polycarboxylic material during repickle and then proceed tanning process. All the data were analyzed by descriptive data analysis and Independent Sample T-Test analysis. The results showed that chrome absorption into chromium was higher when using tanning system exhausted tannery. The difference between two types of tanning process by polycarboxylic material and without polycarboxylic material (conventional tanning) was very significant with significance of P < 0.01. The shrinkage temperature for skin with exhausted system tanning has a higher value than conventional tanning system. It can be said that exhausted tanning system can be used for eco-friendly tanning system.